Physical sciences teachers’ perspectives on implementing learning style-based instructional strategies in science classrooms: Challenges and opportunities - Sakyiwaa Boateng (Journal of Pedagogical Research)
This study investigates the perspectives of physical sciences teachers regarding implementing learning style-based instructional strategies [LSBIS] in science classrooms in South Africa. The aim is to identify the challenges and opportunities associated with integrating these strategies into teaching practices. Research on learning styles and instructional strategies that cater to different cognitive, affective, and physiological factors affecting how individuals learn and how teachers incorporate these into classroom teaching has received considerable focus in educational studies. The implementation of LSBIS in science education is still a subject of discussion, especially regarding its feasibility and efficiency. The study is framed within the Felder-Silverman Learning Style Model and the Social Constructivism Theory. A qualitative multiple case study design was utilised. Four physical sciences teachers from four schools in one education district were purposefully sampled to participate in the study. The interview was the main data collection tool. Data was analysed using the framework as advised by Creswell. The findings reveal a spectrum of perspectives regarding integrating learning style-based instructional strategies. While some teachers express enthusiasm and confidence in utilising these approaches to cater to diverse learner needs and enhance engagement, others voice scepticism and reservations about their utility and feasibility within the constraints of curriculum demands, classroom dynamics and limited resources. The findings illustrate the need for teachers to stress the need to be flexible and adaptable in teaching methods, promoting a blended approach that combines aspects of individualised education while aligning with curricular goals. Collaborative professional development programmes and access to pedagogical materials are crucial for improving teachers' ability to execute successful LSBIS. The study emphasises the need to have a detailed understanding and thoughtful consideration when applying LSBIS in science education. Therefore, it is recommended that teachers take a holistic approach that incorporates ideas from many educational philosophies and research findings on LSBIS, instead of using a uniform one-size-fits-all method in their science classrooms.